Camillo Sitte and Otto Wagner: Contrasting Theoretical Positions towards Modern Cities - Panin, Tonkao; Preamechai, Sarawut (NAJUA: Architecture, Design and Built Environment, 2017)
This paper aims to investigate contrasting theoretical positions of the late nineteenth century between Camillo Sitte and Otto Wagner. While the face of Europe was being transformed in terms of its planning, there were theorists who sought to make sense of the changing social and cultural landscape and attempted to find some way to reconcile the past with the new conditions of living. Among such theorists were Camillo Sitte and Otto Wagner. Although differ, their views played a radical role and helped shape the beginning of modern city planning. This paper will investigate the differences in their views that in many ways have been translated into diverse urban planning ideologies relating to the question of public space and the fabric of the city.